Pengaruh Penambahan Sari Wortel (Daucus Carota, L) Pada Pengencer Terhadap Kualitas Spermatozoa Ayam Kampung Selama Penyimpanan - Hardiyanti Hardiyanti; Muhammad Erik Kurniawan (Faculty of Agriculture, Musamus University, 2020)
This study aims to determine the effect of adding carrot juice on the spermatozoa quality of native chickens, as well as to determine the concentration of carrot juice which is good for maintaining the quality of native chicken spermatozoa during storage. This study used a completely randomized design (CRD) with a nested pattern where the carrot extract concentrations used were 0%, 5%, 10%, 15%, and 20% with 5 treatments and 5 replications. Parameters observed were motility, abnormalities, and longivitas spermatozoa during storage hour-0, 24, 48, 96, and 120 at a temperature of 5°C. The results of this study showed that sperm motility at 0 h 74.00 ± ± 2:30 14.74-96.00% and decreased to 1.60-13.40% at 120 hours of storage. Spermatozoa longivity 125.6-163.00 hours. The conclusion of this study is the addition of carrot juice with different concentrations has a significant effect on the quality of free-range chicken spermatozoa and the best concentrations of 5%, 10%, and 15% were used.